Analysis of Factors Influencing the Intention of Indonesians to Invest in Retail Green Sukuk - Mas DHIRADHARANA; Sri DARYANTI (Communications of International Proceedings, 2020)
This research aims to analyze the explanatory variables of the intention to invest in Retail Green Sukuk, an investment product offered by the Directorate General of Budget Financing and Risk Management (DGBFRM), Ministry of Finance of the Republic of Indonesia. In the relationship model proposed, the intention to invest in Retail Green Sukuk can be explained by three variables: the socially responsible consumption of individuals; their perception of personal gain; and their perception of the effectiveness of their actions. The relationships between the variables were analyzed using the Partial Least Squares – Structural Equation Modeling technique. The data were collected through a survey involving 265 respondents in Indonesia who had purchased financial or investment products. Based on the results, the intention to invest in Retail Green Sukuk is explained by the proposed explanatory variables. The socially responsible consumption habits of investors and their perception of the effectiveness of Retail Green Sukuk have a direct and positive effect on the intention to invest in the product. However, the perception of personal gain only has an indirect effect on the intention through the mediation of the perception of the effectiveness of actions. These findings should be taken into account by DGBFRM when designing marketing and communication strategies for Retail Green Sukuk.
Keywords: Retail Green Sukuk; Partial Least Squares; Socially Responsible Consumption; Consumer Behavior; Socially Responsible Investment